RSS and inertial navigation based indoor localization - Chow, Joel Kin Hung (Nanyang Technological University, 2022)
Indoor localization has been gaining popularity, with its potential use cases it offers due, to the rise of Internet of Things (IoT) and drive for ubiquitous connectivity. On the other hand, recent advancements on phone inertial measurement unit has increased significantly, resulting in more accurate measurements.